Disadvantaged by degrees? How widening participation students are not only hindered in accessing HE, but also during – and after – university. (3rd July 2017) - Budd, Richard
ABSTRACT: There is no shortage of literature addressing the range of reasons why more disadvantaged groups are underrepresented in higher education – and particularly elite universities – in the UK, and it is clear that this has little to do with any real deficiency in terms of ability. This paper begins with an overview of this issue but then extends the argument beyond widening participation (WP) at the point of access. It raises concerns emerging from two relatively underresearched areas in the literature which indicate that 'WP' students are faced with greater inequalities than their more affluent peers both during their undergraduate degrees as well as beyond them. Although the focus here is on the UK, this topic and many of its themes will be familiar to educationalists and HE practitioners in other countries.